Dst Data Evaluation In Practice - Herlan Adim (Scientific Contributions Oil and Gas, 2002)
Originally Drill Stem Test (DST), as an evaluation tool, was only an indicator of type of fluid production. Interest in the DST as a modern evaluation tool was revived when certain theoretical equations were proven as a means of calculating values for important formation parameters. This paper is an example, the basic interpretation method, that will prepare the geologist and engineer for more sophisticated approaches that are sure to come, It is proposed of this paper to show how DST data might be Ned to make certain reservoir parameter de- terminations, in field works.